2018
DOI: 10.1111/cdev.13159
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic‐Phonological Mapping and the Emergence of Visual Expertise for Print: A Developmental Event‐Related Potential Study

Abstract: The N1 effect is an electrophysiological marker of visual specialization for print. The phonological mapping hypothesis (Maurer & McCandliss, 2007) posits that the left‐lateralized effect reflects grapheme‐phoneme integration. In this event‐related potential study, first (age = 7.06 years, N = 32) and third‐grade readers (age = 9.29 years, N = 28) were presented with pairs of pseudowords and Armenian character strings in a novel implicit same‐different paradigm. To test the phonological mapping hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Thus, greater responses to words in our control sample can indicate that audiovisual presentation of words engages reading-related processes automatically. These findings are in accordance with the results of Varga et al (2020) who reported enhanced N1 effect for audiovisual presentation compared to visual only presentation in typically developing children.…”
Section: Letter Position and Letter Identity Encoding Is Similar In Readers With And Without Dyslexiasupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, greater responses to words in our control sample can indicate that audiovisual presentation of words engages reading-related processes automatically. These findings are in accordance with the results of Varga et al (2020) who reported enhanced N1 effect for audiovisual presentation compared to visual only presentation in typically developing children.…”
Section: Letter Position and Letter Identity Encoding Is Similar In Readers With And Without Dyslexiasupporting
confidence: 93%
“…This coarse-grade sensitivity emerges during reading acquisition. Although this is absent in kindergarten children (Maurer et al, 2005b), it emerges after one year of reading instruction (Eberhard-Moscicka et al, 2015;Varga et al, 2020) and follows an inverted U shape pattern which peaks during reading acquisition and then declines over instruction (Fraga-González et al, 2021). The N1 for print is more pronounced over the left posterior-occipital regions (Maurer et al, 2005a;Yoncheva et al, 2010), and this left lateralization is enhanced with reading experience.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the fast development of script expertise has been studied in several laboratories. Varga, Tóth, and Csépe (2020) showed that tuning for print is a fast process and emerges as early as grade 1. Moreover, tuning for familiar letter strings can be enhanced by the parallel presentation of print and sound, suggesting an important role of orthographic-phonological mapping in print awareness development.…”
Section: Looking Into the Future: Brain Research Issues And The Contribution Of Neurosciencementioning
confidence: 99%
“…That is, whereas the perceptual span of beginning readers is generally considered as being smaller than the perceptual span in adults (see Grainger, Dufau, & Ziegler, 2016), beginning readers were able to simultaneously process all letters of a word. Some research using ERPs reported a rapid emergence of print tuning in the first years of reading instructions (Cao, Li, Zhao, Lin, & Weng, 2011; Maurer et al, 2006; Varga, Tóth, & Csépe, 2020). Furthermore, Grainger et al (2012) found that effects of transposed‐letters in masked priming paradigm (i.e., jugde‐JUDGE) were already present in Grade 2, suggesting that the process of accessing abstract orthographic representations is rapidly established during the first years of reading acquisition (see also Acha & Perea, 2008; Ziegler et al, 2014; Perea, Mallouh, & Carreiras, 2013, for similar evidence in Arabic).…”
Section: Introductionmentioning
confidence: 99%